Brazilian guidelines for diagnosis, treatment and follow-up of primary cutaneous melanoma - Part II - Castro, Luiz Guilherme Martins; Duprat Neto, João Pedreira; Di Giacomo, Thais Helena Bello; Messina, Maria Cristina de Lorenzo; Macarenco, Ricardo Silvestre e Silva; Gontijo, Gabriel; Bakos, Renato Marchiori; Bittencourt, Flávia Vasques; Serpa, Sérgio Schrader; Loureiro, Walter Refkalefsky; Stolf, Hamilton Ometto [UNESP] (FapUNIFESP (SciELO), 2016)
The last Brazilian guidelines on melanoma were published in 2002. Development in diagnosis and treatment made updating necessary. The coordinators elaborated ten clinical questions, based on PICO system. A Medline search, according to specific MeSH terms for each of the 10 questions was performed and articles selected were classified from A to D according to level of scientific evidence. Based on the results, recommendations were defined and classified according to scientific strength. The present Guidelines were divided in two parts for editorial and publication reasons. In this second part, the following clinical questions were answered: 1) which patients with primary cutaneous melanoma benefit from sentinel lymph node biopsy? 2) Follow-up with body mapping is indicated for which patients? 3) Is preventive excision of acral nevi beneficious to patients? 4) Is preventive excision of giant congenital nevi beneficious to patients? 5) How should stages 0 and I primary cutaneous melanoma patients be followed?.
Keywords: Dermoscopy; Diagnostic imaging; Diagnostic techniques and procedures; Guideline; Histology; Melanoma; Sentinel lymph node biopsy